Traditional belief and practice on postpartum care recovery among mothers in East Coast of Peninsular Malaysia - Salehudin, Saezah; Abdul Ghani, Radiah (2017)
Background: Postpartum care is highly important to prevent maternal and infant morbidity. In Malaysia, there are several traditional postpartum care practices by mothers. Different states adopted different ways to perform those practices. In spite of long and established practices in Malaysia, its effect and safety profile is not well understood. This study aims to gain an understanding of the traditional practices that Malay women follow in relation to postpartum care and the rationales underpinning such practices. Method: A cross sectional study (n=100) was conducted using self-administered questionnaire consists of demographic information, practice of postpartum care and knowledge of postpartum care. Data was analyzed using Statistical Package Social Software (2.0). Results: The findings shown that, there was no significant association of socio-demographic data with confinement period (p>0.05). For postpartum dietary practice, there were only association between age and encourage more water intake (p=0.047, p<0.05) and also between number of children and prohibit greasy food (p=0.032, p<0.05). For association between socio-demographic data and postpartum physical practice, there was only association between age and body scrub (p=0.046, p<0.05). The most significant factor that influenced postpartum care practice and its knowledge was family tradition with 83% and 97%, respectively. Other activities involved not exposing the body to heat loss by keeping covered, not shampooing the hair, avoiding the wind and sexual abstinence. Mothers and mothers-in-law were most influential in recommending these behaviors. Conclusion: Traditional postpartum care practice is still significant and dominant among mothers in Kuantan, Pahang. This information is important for health care professional to educate women and provide strategies to help them to integrate their beliefs and the practices recommended in contemporary health care practice.